Effectiveness of Celebrity Endorsements in Brand Recall and Purchase Decision - Mittal, Manish; Tulsiyan, Praneet (Indian Journal of Marketing, 2009)
A celebrity endorser is someone who enjoys public recognition and who uses that recognition on behalf of a consumer good by appearing with it in an advertisement. Celebrity endorsement has become one of the most important communication tools for all the companies. Three variables have been identified as important for successful celebrity endorsements physical attractiveness of the celebrity, source credibility (trustworthiness and expertise) of the celebrity, and celebrity/brand congruency. The present paper studies the Effectiveness of Celebrity Endorsements in Brand Recall and Purchase Decision among Indian Consumers and employs primary data collected through a structured questionnaire. It uses non probabilistic convenient sampling to select the respondents. All the respondents were residents of Indore city in Central India and the survey was carried out in January-March 2008. The study suggests that celebrity endorsements are effective in Brand recall but are not effective in motivating people to buy the endorsed product. Celebrity-Brand fit is also important for successful celebrity endorsement.